2001
DOI: 10.1161/hs0901.095382
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Matrix Metalloproteinase-1, -3, -9, and -12 Genes in Relation to Subarachnoid Hemorrhage

Abstract: Background and Purpose-Intracranial aneurysm, which underlies the vast majority of subarachnoid hemorrhage incidences, has a multifactorial etiology, and the importance of genetic factors is increasingly recognized. Development and rupture of intracranial aneurysms involve degradation and remodeling of the vascular wall matrix in which the matrix metalloproteinases (MMPs) play an important role. The possible impact of MMP gene polymorphisms on susceptibility to intracranial aneurysms is still controversial, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 56 publications
3
46
1
Order By: Relevance
“…A total of five populations (N = 729) were included in the database and used for further analysis. These populations included individuals from France and England (Zhang et al, 2001;Lamblin et al, 2002), Japan and Korea (Maeda et al, 2001;Lee et al, 2010), and the African-American population from the USA (Ferrand et al, 2002). Population subdivision was assessed by analysis of molecular variance (AMOVA) using ethnicity as subdivision criteria with the Arlequin Software v.3.5.…”
Section: Comparison With Other Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of five populations (N = 729) were included in the database and used for further analysis. These populations included individuals from France and England (Zhang et al, 2001;Lamblin et al, 2002), Japan and Korea (Maeda et al, 2001;Lee et al, 2010), and the African-American population from the USA (Ferrand et al, 2002). Population subdivision was assessed by analysis of molecular variance (AMOVA) using ethnicity as subdivision criteria with the Arlequin Software v.3.5.…”
Section: Comparison With Other Populationsmentioning
confidence: 99%
“…We compared our data with those of Asian (Japanese and Korean populations), European (French and English populations), and African-American (USA) populations (Maeda et al, 2001;Zhang et al, 2001;Ferrand et al, 2002;Lamblin et al, 2002;Lee et al, 2010). The first component separated Mestizo, Mazahua, Asian, African-American, and French populations from the rest.…”
Section: Comparison With Other Populationsmentioning
confidence: 99%
“…7) However, high levels of MMP-2 and -9 have been detected in various types of structurally unstable vasculature including cerebral aneurysms, atherosclerotic carotid arteries, and brain arteriovenous malformations. 9,15) Previously, we reported increased endothelial expression of MMP-2 and -9, and tissue inhibitors of metalloproteinase (TIMP)-2 in cerebral cavernous malformations with hemorrhage, 6) suggesting involvement in the pathophysiology of cavernous malformations.…”
Section: Introductionmentioning
confidence: 99%
“…Elastin and collagens are major structural components of the vascular wall, and it has been suggested that elastinolysis is particularly pertinent to vessel dilation, while collagenolysis relates to aneurysm rupture. 45 Inrecentyears,compellingevidencehasindicatedthat a number of matrix metalloproteinases (MMPs), which possess proteolytic activity against extracellular matrix proteins such as elastin and collagens, play an important roleinthediseaseetiopathologyofvarioustypesofaneurysms. 45 Although the genetic basis of CA is poorly understood, the identification of susceptible genetic variants may increase our understanding of CA formation and rupture mechanisms.Extensivegeneticassociationstudiesareurgently needed to elucidate the molecular pathogenesis of CAs.…”
mentioning
confidence: 99%
“…45 Inrecentyears,compellingevidencehasindicatedthat a number of matrix metalloproteinases (MMPs), which possess proteolytic activity against extracellular matrix proteins such as elastin and collagens, play an important roleinthediseaseetiopathologyofvarioustypesofaneurysms. 45 Although the genetic basis of CA is poorly understood, the identification of susceptible genetic variants may increase our understanding of CA formation and rupture mechanisms.Extensivegeneticassociationstudiesareurgently needed to elucidate the molecular pathogenesis of CAs. 46 In recent years, candidate gene association studies havebeenthemostcommonapproachtoidentifysusceptibilitygenesforcomplexdiseasessuchasCA.However, our ability to identify relevant candidates is generally restricted by our understanding of disease pathophysiology, which in many cases is limited.…”
mentioning
confidence: 99%